Impact of blended learning (OMO) on Japanese language students at Hong Bang International University - Hung, Nguyen Minh; Trinh, Ho Le Thi Xuan (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
This study explores learners’ opinions and their experiences on Online Merging Offline (OMO) blended learning model on the quality of student learning in the Japanese Language Department at Hong Bang International University. Implemented with a 70% offline and 30% online blended learning model during the first semester of the 2023-2024 academic year, the study evaluates student perceptions and identifies areas for improvement. Data were collected through surveys, in-depth interviews, and observations involving second to fourth-year students. The findings reveal a generally positive reception towards the OMO model, with students appreciating the flexibility, convenience, and enhanced interaction provided by the blended format. Access to diverse learning resources and support from instructors and institutional facilities improved learning experiences. However, challenges such as group dynamics, self-discipline, and effective utilization of AI tools were noted. About 30% of students reported no significant improvement in self-directed learning, and some felt overwhelmed by the abundance of resources. Recommendations include ongoing implementation with improvements based on feedback, additional training for instructors, and ensuring robust technological support. Addressing scheduling issues and establishing a continuous feedback mechanism are also crucial. Encouraging extracurricular activities and promoting creativity among both instructors and students can further enrich the learning environment. By adopting these recommendations, Hong Bang International University can refine its blended learning approach, ensuring it meets educational goals and enhances the overall learning experience. This study underscores the importance of adapting to technological advancements and leveraging them to optimize higher education in the 4.0 era.